Influencia de la racionalidad, extroversión, neurosis e impulsividad en el consumo de los estudiantes de la Universidad Nacional de Chimborazo, periodo 2020 – 2021. - Holger Santiago, Coca Chiluiza (2021)
ABSTRACT This research work analyzes the consumption of the students of the Universidad Nacional de Chimborazo in the year 2021, focusing the study on determining whether economic variables, psychological variables or both influence their consumption decisions. The analysis was carried out by applying Arnold Zellner's Seemingly Unrelated Equations Estimator (SURE), where the main results were that only the economic variables used influence student consumption, however, the incorporation of psychological variables improves the explanatory capacity of the model. For a theoretical support, the main contributions of the Microeconomic Theory of Consumption were collected, addressing issues such as consumer theory, budget restrictions, marginal utility and correct economic rationality. Subsequently, the main contributions of the theory of Economic Psychology, as well as its main authors, were synthesized. Consequently, after defining the theory, the most relevant studies in this area were collected and their results were presented. For the application of the SURE Estimator, the existence of correlation between the stochastic perturbations of the equations proposed in the STATA statistical package was verified, which is the main conditioner for using this estimator. The results of the statistical tests gave way to the application of the estimator, where it was evidenced that its application improves the level of significance of the variables used, with respect to the application of Ordinary Least Squares. Keywords: Homo Economicus, Economic Psychology, Seemingly Unrelated Equations, Microeconomic Theory of Consumption, Psychological Variables. Reviewed by: Dr. Narcisa Fuertes, PhD. ENGLISH PROFESSOR cc: 1002091161